Tumor-targeted co-delivery of mitomycin C and 10-hydroxycamptothecin via micellar nanocarriers for enhanced anticancer efficacy1. Issue 29 (2nd April 2015) - Lin, Jinyan; Li, Yang; Wu, Hongjie; Yang, Xiangrui; Li, Yanxiu; Ye, Shefang; Hou, Zhenqing; Lin, Changjian
<x xml:space="preserve">Abstract</x> Polymer–lipid hybrid micelles co-delivered hydrophilic mitomycin C and hydrophobic 10-hydroxycamptothecin showed improved cellular uptake and cytotoxicity in vitro and enhanced tumor accumulation and antitumor activity in vivo.